Female Genital Mutilation: perceptions of healthcare professionals and the perspective of the migrant families - Kaplan-Marcusán Adriana; del Rio Natividad; Moreno-Navarro Juana; Castany-Fàbregas Ma José; Nogueras Marta; Muñoz-Ortiz Laura; Monguí-Avila Eliana; Torán-Monserrat Pere (BMC, 2010)
Abstract Background Female Genital Mutilation (FGM) is a traditional practice which is harmful to health and is profoundly rooted in many Sub-Saharan African countries. It is estimated that between 100 and 140 million women around the world have been victims of some form of FGM and that each year 3 million girls are at risk of being submitted to these practices. As a consequence of the migratory phenomena, the problems associated with FGM have extended to the Western countries receiving the immigrants. The practice of FGM has repercussions on the physical, psychic, sexual and reproductive health of women, severely deteriorating their current and future quality of life. Primary healthcare professionals are in a privileged position to detect and prevent these situations of risk which will be increasingly more present in Spain. Methods/Design The objective of the study is to describe the knowledge, attitudes and practices of the primary healthcare professionals, working in 25 health care centres in Barcelona and Girona regions, regarding FGM, as well as to investigate the perception of this subject among the migrant communities from countries with strong roots in these practices. A transversal descriptive study will be performed with a questionnaire to primary healthcare professionals and migrant healthcare users. Using a questionnaire specifically designed for this study, we will evaluate the knowledge, attitudes and skills of the healthcare professionals to approach this problem. In a sub-study, performed with a similar methodology but with the participation of cultural mediators, the perceptions of the migrant families in relation to their position and expectancies in view of the result of preventive interventions will be determined. Variables related to the socio-demographic aspects, knowledge of FGM (types, cultural origin, geographic distribution and ethnicity), evaluation of attitudes and beliefs towards FGM and previous contact or experience with cases or risk situations will be obtained. Discussion Knowledge of these harmful practices and a preventive approach from a transcultural perspective may represent a positive intervention model for integrative care of immigrants, respecting their values and culture while also being effective in eliminating the physical and psychic consequences of FGM.